2001
DOI: 10.7705/biomedica.v21i3.1117
|View full text |Cite
|
Sign up to set email alerts
|

Participación del polimorfonuclear neutrófilo en la respuesta inmune contra Paracoccidioides brasiliensis

Abstract: ~o@oración para lnvestigaciones ~ibló~icas, Medellín, ~olombii. Vscuela de Bacteriología y Laboratorio Clínico, Universidad de Antioquia, Medellín, Colombia La paracoccidioidomicosis, micosis profunda de gran importancia en Latinoamérica, se caracteriza por presentar una respuesta inflamatoria aguda en el pulmón, órgano blanco del proceso infeccioso. En las etapas iniciales, esta respuesta se caracteriza principalmente por un infiltrado de polimorfonucleares neutrófilos (PMN), los que, de acuerdo con estudios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Several studies have been highlighting the importance of neutrophils in the pathogenesis of PCM, most of them dedicated to evaluate the role of these cells during early stages of infection and their influence on the adaptive immune response [ 8 , 11 , 12 ]. However, to our knowledge, there are no studies focused on evaluating neutrophil involvement in the chronic stages or in the development of fibrosis observed in this mycosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been highlighting the importance of neutrophils in the pathogenesis of PCM, most of them dedicated to evaluate the role of these cells during early stages of infection and their influence on the adaptive immune response [ 8 , 11 , 12 ]. However, to our knowledge, there are no studies focused on evaluating neutrophil involvement in the chronic stages or in the development of fibrosis observed in this mycosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated the relevance of neutrophils in the pathogenesis of PCM, especially during the early stages of infection [ 7 , 8 ]. Recently, it has been suggested that neutrophils may modulate the innate and adaptive immune response against P .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding PF due to P. brasiliensis infection, a strategy using a mAb specific to neutrophils was employed [10,11]. It has been described that neutrophils play an important role in the pathogenesis of PCM; thus, these phagocytic cells exert a protecting effect during the early stages of infection [66], as well as being relevant during the chronic stage of the mycosis as they are present in high numbers accompanying the granulomatous lesions [8,23,67]. With this in mind, P. brasiliensis-infected mice were treated with a mAb specific to neutrophils at four weeks post-infection (when the fibrotic process begins) followed by doses every two days for two weeks.…”
Section: Immunotherapy or Antibody-based Therapymentioning
confidence: 99%
“…Similarly, it has been suggested that neutrophils are essential during the acute inflammatory phase since they represent more than 85% of inflammatory cells and could positively modulate the innate immune response through the production of proinflammatory cytokines and lipidic mediators in the infected lung tissue (Gonzalez and Cano, 2001;Gonzalez et al, 2003;Balderramas et al, 2014). Along these lines, using an experimental model of pulmonary PCM in mice with intermediate susceptibility to infection and treated with a monoclonal antibody specific to neutrophils, we reported that compared to control mice, infected and neutrophil-depleted mice showed decreased survival rates during the early stage of infection, accompanied by an increase in both the fungal burden and the inflammatory response with an exaggerated production of several chemokines and proinflammatory cytokines, suggesting the pivotal role of these phagocytic cells in this fungal infection during the early course of infection (Pino-Tamayo et al, 2016).…”
Section: Paracoccidioidomycosismentioning
confidence: 99%
“…In the case of systemic and endemic mycoses, there are scant studies that link the IL-17 and/or neutrophils with the development of a chronic inflammatory process or with fibrosis development. Some studies have demonstrated the presence of neutrophils in pulmonary infiltrating cells during infections by P. brasiliensis (Gonzalez and Cano, 2001;Gonzalez et al, 2003), H. capsulatum (Baughman et al, 1986), C. posadasii (Hung et al, 2005), and B. dermatitidis (Lorenzini et al, 2017). However, as mentioned above, the role of neutrophils during these dimorphic fungal infections is not clear; moreover, their participation in the immune response appears to depend on the phase of infection (acute or chronic) (Pino-Tamayo et al, 2016;Puerta-Arias et al, 2016).…”
Section: Neutrophils and Il-17 Participation In The Granulomatous Infmentioning
confidence: 99%